Reina Lewis, Rethinking Orientalism. Women, Travel and the Ottoman Harem (Altre Modernità, 2012)
Reina Lewis, Rethinking Orientalism. Women, Travel and the Ottoman Harem(New Brunswick, Rutgers University Press, 2004, pp. 297ISBN 0813535433)di Ester Gendusa